THE CRITICAL THINKING SKILL REPRESENTATIONS OF PROFIL PELAJAR PANCASILA CHARACTER IN ENGLISH TEXTBOOK "WORK IN PROGRESS'' FOR TENTH GRADE OF HIGH SCHOOL - Ika Erwita Zebua; Afore Tahir Harefa; Yaredi Waruwu; Trisman Harefa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Critical thinking is the ability to objectively assess information to reach logical conclusions. In the 21st century, this skill is essential for students to face global challenges. This study analyzed the representation of critical thinking indicators in the "Work in Progress" English textbook for Grade X used at SMK Swasta Pembda Nias. A qualitative content analysis method was applied, with data collected through documentation and analyzed in five stages: familiarization, coding, reduction, interpretation, and representation. The findings revealed that the three indicators of critical thinking from the Profil Pelajar Pancasila were present: acquiring and processing information (25%), analyzing and evaluating reasoning (52%), and reflecting on one own thinking (23%). The second indicator was most dominant. Additionally, implicit meaning delivery (52%) appeared slightly more frequently than explicit (48%). These results indicate that the textbook sufficiently supports the development of students critical thinking skills in line with the Profil Pelajar Pancasila.